2019
DOI: 10.1016/j.bbi.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory agents for smoking cessation? Focus on cognitive deficits associated with nicotine withdrawal in male mice

Abstract: Nicotine withdrawal is associated with cognitive deficits including attention, working memory, and episodic memory impairments. These cognitive deficits are a hallmark of nicotine abstinence which could be targeted in order to prevent smoking relapse. The underlying mechanisms, however, are poorly understood. In this study, memory impairment was observed in mice 4 days after the precipitation of nicotine withdrawal by the nicotinic antagonist mecamylamine. The presence of cognitive deficits correlated with mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…In addition, withdrawal from nicotine leads to a diverse array of clinical symptoms, spanning cognitive, affective, and motivational domains. A recent study using a model of precipitated nicotine withdrawal showed that elements of cognitive disruption in this model correlate with microglial activation in the hippocampus and prefrontal cortex ( 59 ). However, it is important to note that mecamylamine, which is used in the precipitated withdrawal model, has cognitive-depressive effects on its own in rodents ( 60 ), monkeys ( 61 ), and even humans ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, withdrawal from nicotine leads to a diverse array of clinical symptoms, spanning cognitive, affective, and motivational domains. A recent study using a model of precipitated nicotine withdrawal showed that elements of cognitive disruption in this model correlate with microglial activation in the hippocampus and prefrontal cortex ( 59 ). However, it is important to note that mecamylamine, which is used in the precipitated withdrawal model, has cognitive-depressive effects on its own in rodents ( 60 ), monkeys ( 61 ), and even humans ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Object recognition memory was assessed with the V-maze (Panlab, Barcelona, Spain) to measure cognitive performance, as previously described (Puighermanal et al, 2009; Saravia et al, 2019). V-maze consisted on an apparatus made of black plexiglass with two corridors (30 cm long × 4.5 cm wide) set in V with a 90° angle and 15 cm-high walls.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have also demonstrated that CBD exerted a neuroprotective effect against the adverse consequences of alcohol in the hippocampus [46] and reduced the microglia reactivity induced by nicotine withdrawal. This attenuated the increase in the levels of neuroinflammatory markers IL1β in the hippocampus and IFNγ in the PFC [100]. According to these data, it could be hypothesized that CBD may prevent the microglial reactivity and neuroinflammation induced by cocaine.…”
Section: Possible Mechanisms Involved In the Protective Effects Ofmentioning
confidence: 99%
“…In mice, the pre-treatment with an intermediate dose of CBD (20 mg/kg) for 10 days facilitated the novel object recognition task and increased learning markers, such as BDNF expression and neural progenitor proliferation in the hippocampus [54]. CBD blunted the cognitive impairment induced by THC in an adenosine A2A receptor-dependent manner [113] and abolished the memory impairment in the object recognition task induced by nicotine withdrawal (precipitated by the administration of the nicotinic antagonist mecamylamine) as well as the neuroinflammatory response and the impairment in neurogenesis associated with these cognitive deficits (as previously commented) [100].…”
Section: Possible Mechanisms Involved In the Protective Effects Ofmentioning
confidence: 99%